The Banking Act of 1935 - Gayer, A. D. (Quarterly Journal of Economics, 1935)
I. The Conditioning Economic Context, 97.— II. Federal Deposit Insurance, 99.— III. General Nature of Federal Reserve Law Amendments, 104.— IV. Changes in the Organization of the Federal Reserve System, 107.— V. The Instruments of Credit Control, 109.— VI. The Dilemma of Credit Policy, 114.